Public Preferences Towards Car Sharing Service: The Case of Djibouti - Ali Aden, Waiss; Zheng, Jianfeng; Ullah, Irfan; Safdar, Muhammad (Frontiers in Environmental Science, 2022)
This study aims to investigate the preference, willingness, and concern of the traveler toward car-sharing services in Djibouti. Potential benefits of car sharing are controlling severe congestion, immobility, excessive vehicle ownership, parking issue, and reduced GHG. The authors conducted a stated preference (SP) survey to explore travelers' perceptions. The questionnaire was distributed online through Google form. The orthogonal design was used for survey design and the final questionnaire was distributed online through the Google form. The questions included the awareness of car-sharing services, attributes related to transport modes, and demographic characteristics. A total of 600 respondents were received. Two modeling techniques (discrete choice model and Machine learning (ML) models) were used in this study. In discrete choice, the mixed multinomial logit model was employed for evaluation and analysis. The result showed that demographic characteristics like gender, age, education, income are significant, while attributes related to a transport mode like travel time, travel cost, registration fee were found significant. In ML, three different models (AdaBoost, decision tree, and neural network) were used. The result indicates that the ML models generally performed well. According to the goodness-of-fit results, the AdaBoost model has the highest accuracy. This study could be helpful to transport planners and policymakers for the implementation of car-sharing services in urban areas.